L’identification de systèmes ou de théories dans les œuvres du ius commune - Florian Reverchon (Clio@Themis)
Restituting the dogmatic elaborations of the authors of the ius commune sometimes involves a systematic approach that seems unfaithful to the sources. Using the example of the nullitas of juridical acts, this article considers the identification of theories in the works of learned law. The link between the common conception of nullity as an ontological defect and the technical discourse on the nullity of prohibited acts led to constructions that can be described as theories. They address the question of how norms fit into the legal order, and thus the coherence of the law.